Upaya Meningkatkan Keterampilan Praktik Sholat Melalui Metode Demonstrasi Dipadu Media Peraga Visual Di Sdn 22 Batang Tuhur Kec. Dua Koto Kab Pasaman - Lubis, Arlan (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students’ prayer practice skills through demonstration methods and visual aids. The research was conducted in two cycles, with the first cycle showing suboptimal results, where some students struggled to perform prayer movements correctly. In the second cycle, improvements were made by using more varied visual media and a group-based learning approach. The results showed a significant increase in students’ prayer practice skills, with 93.3% of students achieving a high level of accuracy in the prayer movements. The study concludes that the combination of demonstration methods and visual aids is effective in enhancing students’ understanding and practical skills in performing prayer.